Economic evaluation of rotavirus vaccination for Malaysia / Tharani Loganathan - Tharani, Loganathan (2016)
Rotavirus infection is an important cause of severe diarrhoea among children under-five years worldwide. Two rotavirus vaccines are available worldwide, that are safe, efficacious and recommended by the World Health Organization for inclusion into national immunisation programmes. Although widely regarded as cost-effective interventions, rotavirus vaccines are expensive. Vaccine introduction has been slow in middle-income countries like Malaysia, with low rotavirus mortality. Hence, an economic evaluation is necessary to inform evidence-based policy making surrounding the inclusion of rotavirus vaccines into the Malaysian national immunisation programme. In this thesis, a conceptual framework was developed for the economic evaluation of rotavirus vaccines in Malaysia. The burden of rotavirus was estimated, followed by the assessment cost-effectiveness, affordability and the benefits of rotavirus vaccines in providing financial risk protection and enhancing equity in Malaysia. The health and economic burden of rotavirus gastroenteritis in Malaysia was estimated using multiple local data sources. Cost-effectiveness of rotavirus vaccines was evaluated from the healthcare provider and societal perspectives, using an age-structured, multi-cohort model. A budget impact analysis was conducted to assess the affordability of a universal rotavirus vaccination programme to the Ministry of Health, Malaysia. As Malaysia has not determined a threshold for cost-effectiveness of interventions, this thesis explores vaccine price and affordability, at various cost-effectiveness thresholds suggested for Malaysia. A two-year prospective, hospital-based rotavirus study conducted at two public hospitals in Malaysia provided patient-level data for the exploration of illness-related healthcare expenditure and its impact on household income. On identifying income-related inequities in out-of-pocket healthcare payments for rotavirus gastroenteritis, an extended cost-effectiveness analysis was conducted to evaluate the distributional benefits of universal rotavirus vaccination in averting illness and providing financial risk iv protection in Malaysia. This thesis found that rotavirus gastroenteritis results in a substantial health and economic burden in Malaysia, much of which was previously overlooked. Both rotavirus vaccines are likely to be cost-effective and affordable to the Ministry of Health, Malaysia, at prices negotiated in line with international tenders. Out-of-pocket healthcare expenditure for rotavirus especially impacts poor households. Universal vaccination would reduce rotavirus episodes and costs among all income groups, while the poor would particularly benefit in terms financial risk protection. The economic evaluation of rotavirus vaccines in this thesis is the first conducted in Malaysia. The evidence gathered here strongly suggests that rotavirus vaccines are a worthy investment for the government of Malaysia. The framework proposed in this thesis for economic evaluations of rotavirus vaccines in Malaysia, may be used for evaluations of other vaccination programmes in Malaysia, or other middle-income countries.